VD_FINDINFO Décision / 2011 / 547 vom 5. Oktober 2011 - VD Tribunal cantonal (2011)
ORDONNANCE DE CONDAMNATION, OPPOSITION TARDIVE | 354 CPP (CH), 356 al. 2 CPP (CH), 393 al. 1 let. b CPP (CH), 88 CPP (CH)